Portable pH meter in use at Althouse Chemical Company plant (1946)
General view of Martin Eby (left) using a portable pH meter at the Althouse Chemical Company manufacturing plant in Reading, Pennsylvania. The photograph also shows several pieces of equipment used in the manufacture of dyestuffs, including a portable pump, mixer, and skid bags of intermediate materials. On the right side of the frame, an unidentified employee is seen transferring cracked ice to a buggy for delivery to the reactors. Based in Reading, Pennsylvania, the Althouse Chemical Company was founded in 1915 by C. Scott Althouse (1880-1970) as a small, family-owned firm specializing in fabric dyes of a superior quality and class. In 1954, the Crompton & Knowles Corporation of Worcester, Massachusetts acquired Althouse, which continued to operate as a division of Crompton & Knowles and a leader in the specialty dyes industry.
Keywords: Dye industry; Scientific apparatus and instruments; Dyes and dyeing; Dyes and dyeing--Equipment and supplies; Althouse Chemical Company